The influence of brand ambassadors and brand trust on purchasing decisions for Wardah products - Rahajeng, Yekti; Nurkinasih, Indah; Elmas, M.Syarif (Central Research Institute for Agriculture (CeRIA), 2024)
This study aims to determine the effect of brand ambassadors and brand trust on purchasing decisions on Wardah products. The type of research used is quantitative research. The type of research used is quantitative research. The sample in this study was 96 people from the population of consumers of Wardah products. The sampling technique was carried out using purposive sampling. The data analysis method in this study uses Statistical Product and Service Solutions (SPSS). The data analysis method used is validity test, reliability test, classical assumption test, multiple linear regression analysis, determination analysis (R2), hypothesis test, which is processed by the SPSS program. The results showed that (1) from the partial test results (t-test) for the brand ambassador variable, the value of t count > t table (15.846 > 1.985) and the significance result of 0.000 < 0.05. This shows that there is a positive and significant influence between brand ambassadors on purchasing decisions on Wardah products in Probolinggo City. (2) from the results of the partial test (t test) for the brand trust variable, the value of t count > t table (3.731 > 1.985) and the significance result of 0.000 < 0.05. This shows that there is a significant influence between brand trust on purchasing decisions on Wardah products in Probolinggo City. (3) the results of the simultaneous test (F test) obtained the value of F count > F table (345,590 > 3.09) and the significance result is 0.000 < 0.05. This shows that brand ambassadors and brand trust together have an effect on purchasing decisions.